2018
DOI: 10.1111/aogs.13339
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for discontinuation of thyroid hormone replacement therapy in early pregnancy: a study from the Norwegian Mother and Child Cohort Study and the Medical Birth Registry of Norway

Abstract: In Norway, around 13% of women with hypothyroidism discontinue THRT in early pregnancy. For discontinuers, non-medicated mental comorbidity and non-compliance with nutritional supplements presented increased risk, whereas having a medicated somatic disorder was protective. Health professionals advising women with hypothyroidism should be aware of risk factors associated with THRT discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In Switzerland, healthcare claims data are underused on an institutional level, and drug utilization on a national level is largely unknown. Other western countries, such as all Scandinavian countries, France, Germany, and the United States, have used healthcare claims data for surveillance of drug use and safety for decades, enhancing them with external data to study vulnerable populations such as pregnant women [40][41][42][43]. The Swiss federal council's health policy strategy 2020-2030 declared that the technological and digital transformation of the healthcare sector was one of its four main goals in order to improve public health over the next decade [44].…”
Section: Discussionmentioning
confidence: 99%
“…In Switzerland, healthcare claims data are underused on an institutional level, and drug utilization on a national level is largely unknown. Other western countries, such as all Scandinavian countries, France, Germany, and the United States, have used healthcare claims data for surveillance of drug use and safety for decades, enhancing them with external data to study vulnerable populations such as pregnant women [40][41][42][43]. The Swiss federal council's health policy strategy 2020-2030 declared that the technological and digital transformation of the healthcare sector was one of its four main goals in order to improve public health over the next decade [44].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][14][15][16][17] We found no difference in fine and gross motor function, communication skills, and behavior. This is important because some women discontinue their THRT upon recognition of pregnancy 37,38 and, among those who are medicated, adherence to THRT is not always optimal. 39 Juch et al 39 found that 17% of pregnant women with hypothyroidism exhibit low adherence during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Only about half of LT4-treated women have high LT4 adherence during pregnancy [42–44,45 ▪ ]. In a Norwegian population-based cohort, 13% of hypothyroid women using thyroid hormone therapy before pregnancy discontinued treatment in early pregnancy [42]. In the same study, 5.8% of women had low adherence, and only 50% had adequate adherence to prescribed thyroid hormone [43].…”
Section: Indications For Treatment Of Maternal Thyroid Hypofunctionmentioning
confidence: 95%
“…Only about half of LT4-treated women have high LT4 adherence during pregnancy [42–44,45 ▪ ]. In a Norwegian population-based cohort, 13% of hypothyroid women using thyroid hormone therapy before pregnancy discontinued treatment in early pregnancy [42].…”
Section: Indications For Treatment Of Maternal Thyroid Hypofunctionmentioning
confidence: 99%
See 1 more Smart Citation